Corporate governance and earnings management struggles: responses to adapt a modern capital mobilisation in the transitional economy - Thi Bich Chi Pham; Ha Linh Nguyen; Thi Minh Thu Vu; Van Tu Truong (Cogent Business & Management, 2022)
As one of the market socialist countries with the dominant power of the government, Vietnam has recognised the importance of the open market with modern corporations regarding capital mobilisation. Up to 2000, Vietnam officially established its stock market showing its openness to a more diverse ownership structure. However, during this transition, the two most prominent issues-the lag of corporate governance practices and earnings management-have created a burden for this young market. In the tendency to join the global economy, this study is conducted to investigate how Vietnamese businesses struggle and overcome those problems. Regression estimators are used to analyse panel data covering the period 2015-2019, and FEM-robust (SE) shows its best fit to the model. The results suggest that to mitigate earnings management, the number of board members should be low, within the optimal span. Foreign ownership with negative sign implies that enhancing the foreign shareholders' roles is essential. In contrast, the lowering of state ownership and concentration ownership ratios-the unique features of a transitional economy-might bring a better mechanism of corporate governance and earnings quality. In addition, policymakers, academics, and practitioners should also consider other explanatory variables when concerning corporate governance as well as the phenomenon of earnings management.
Keywords: 650; corporate governance; earnings management; modern capital mobilisation; Vietnam